The defining moments in Bengal, 1920-1947 - Bhattacharya, Sabyasachi, 1938-
aIn what way was 20th century Bengal different from the late 19th century 'Renaissance' Bengal? How did a regional identity consciousness develop? What social experiences drove the Muslim community's identity consciousness? How did Bengal cope with crises like the inflation during World War II, and the famine of 1943, the communal riots, climaxed by the Calcutta riots of 1946? This book looks at these crises which cast a shadow on the decades that followed the period under study, 1920-1947.